PENGEMBANGAN MEDIA PEMBELAJARAN KELISTRIKAN SEPEDA MOTOR BERBASIS MOBILE APPLICATION ANDROID - Fatkhul Aziz (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to develop and discover the learning media for motorcycle electricity based on android mobile applications. This study uses the type of R&D with the ADDIE model. The subjects of this study were student number 30 ofcclass XI Motorcycle Engineering at SMK Muhammadiyah 1 Muntilan. The object of research is a learning media based on the android mobile application. Data collection techniques using a questionnaire. The data analysis technique used quantitative descriptive. The results of the research are the development of learning media based on Android mobile applications and validation from material experts, namely the average score of 74, from media experts the average score is 53, from the small group trial of 5 students, the average score is 66.2, the large group trial is 30 students, namely the average score. 80.37 as a respondent, it is classified as being in the